Bibliometric Analysis of Improfing Academic Performance in the Era of Industry 4.0: A Scopus-based Mapping (1969-2023) - Mursiti, Tutik; Maksum, Muh. Nur Rochim; Ali, Mohamad; Shohabia, Mahasri; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to map improving academic performance in publications indexed by the Scopus database from 1969 – 2023. 1969 was chosen as the starting year based on findings in the Scopus database that in that year the first publication on improving academic performance was found. The analysis method used is bibliometrics to collect data from the Scopus database from 1969 to 2023 using the Boolean search engine. Data was analyzed using Excel and R/R-Studio. while VOSviewer is used to perform a visual analysis of the simultaneous occurrence of keywords and document quotes. The author found 1,612 publications that matched the specified function, subject, and criteria. The results of this research show an annual growth rate of 9.26%, indicating increasing interest in the topic & quot; Improving Academic Performance & quot; along with the development of the Revolution 4.0 era. The peak publication occurred in 2021. The United States (US) was the country that contributed the most with 560 documents, followed by China with 127 documents, and the UK with 117 documents. The most prolific writer was Bradshaw, CP. Perry, R.P. Skinner, C.H. leading with the number of publications of 4 documents. The authors recommend further research considering other national and international databases. This research provides a brief overview of the literature that can be accessed by researchers interested in "improving academic performance" in the Industrial Revolution 4.0 era and provides recommendations for future research.